Old truths and new clichés - Singer, Isaac Bashevis 1904-1991 (Princeton University Press, 2022)
"This volume collects eighteen essays by Isaac Bashevis Singer (1902-1991), who was awarded the Nobel Prize in Literature in 1978. A prolific author of fiction, memoir, and criticism, Singer wrote primarily in Yiddish, but he translated several dozen of his essays into English to present as lectures at colleges and synagogues throughout his life, especially during the 1960s. Despite his plans to collect and publish these essays before his death, they remained scattered among his other papers when they were donated to the Harry Ransom Center at the University of Texas. David Stromberg, the editor for the Singer estate, has selected essays that represent Singer's fullest treatment of topics he engaged with throughout his life. The volume begins with an autobiographical note, followed by essays grouped by theme: The Literary Arts, Yiddish and Jewish Life, and Personal Writings and Philosophy. Most of the selected essays were originally published in Yiddish or delivered as lectures but have never been published in English before, nor have they been collected in any language. In his introduction, Stromberg explains that in assembling the collection he has tried to include essays that "express a central element of Singer's intellectual foundation - a testament to the spirit and intellect of his artistic vision." In an afterword, Stromberg provides further details on Singer's editorial process and the challenges his archive presents for contemporary scholars and editors"--Provided by publisher.